Early experience in surgical treatment of adolescence idiopathic scoliosis: a report of four cases - Ismail, Mohamad Wafiuddin; Mor Japar Khan, Ed Simor Khan; Karupiah, Rajandra Kumar; Zakaria@Mohamad, Zamzuri; Nusuruddin, Muhammad Haidar; Roslan, Ahmad Faizal; Abd Bakar, Luqman; Yunus, Syafik; Zamri, Fawwaz (Faculty of Medicine & Health Sciences Universiti Malaysia Sabah, 2020)
Adolescent idiopathic scoliosis (AIS) is the most common spinal deformity among teenager. For those indicated, early surgical intervention allows better surgical correction due to flexibility of the spine during teenage years, hence good functional outcome and better cosmetic can be expected. In this case report, there is the management of four patients surgically using the posterior spinal instrumentation and fusion. Pre-operatively patients were examined at IIUM Medical Centre spine clinic, all necessary investigations were carried out. A thorough explanation was done to patient and parents regarding procedure, risk and benefit. All patients were treated using the same surgical technique. Neuromonitoring was used throughout the whole surgery until skin closure. All patients were hospitalized around one week. Post-operatively patients were followed up at two weeks, six weeks, three months, and every six months thereafter. It is important for clinicians to identify patients with AIS as early detection and timely treatment will change the natural history of curve progression. Surgical intervention when necessary will be easier and with less risk of complications when surgery was carried out during teenage years as the spine is more flexible and the deformity is less severe.